Patients and relatives' perspectives about electroconvulsive therapy (ECT) in Khartoum, Sudan - M. Hussein, Omar; KM, Ahmed; IH, Mohammed; Hatta Sidi,; Najmi S, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Lack of knowledge and inappropriate attitude towards electroconvulsive therapy (ECT) treatment may affect the outcome of psychiatric’s morbidity and mortality. However, less systematic studies have been done on this area. This study aimed to assess the patients’ and relatives’ perspectives, i.e. knowledge, attitude and compliance on ECT in Khartoum State, Sudan. This was an observational hospital-based study conducted among 103 psychiatric patients and their relatives respectively who visited the Taha Basher and Eltigani Elmahi psychiatric hospitals during 2016. Both the patients and their relative inquired about different criteria of knowledge and attitude towards ECT. The percentage of score was calculated based on their positive answers by selecting the most appropriate answer or by calculating the mean of many positive answers. All the data were collected through a pre-designed questionnaire, and further analyzed statistically. Male was represented 61 (59.2%) and the commonest age group of patients was 16-30 years. The overall score of knowledge towards ECT among patients and their relative was 54.9% and 59.4%, respectively. Acceptance on the use of ECT were agreed by 43.7% of patients and more than 70% of patients and their relatives believed giving ECT for emergency psychiatric cases. Psychiatrist was the most frequent source of information reported by both patients (73.8%) and relatives (67%). Male relatives showed significantly higher attitude of recommending ECT treatment (p=0.004) for other patients. Patients and their relatives were reported to have moderate and better knowledge and attitude towards the use of ECT, respectively.